(untitled) (Revista Innova Educación, 2025)
The objective of this study is to examine enrollment trends in the Bachelor’s Degree in Basic Education at the Universidad Pedagógica Veracruzana, through the analysis of enrollment statistics at the beginning of courses over the last six academic years (2019–2020 to 2024–2025), in order to identify patterns, associated factors, and their potential impact on educational planning. The study was conducted using a quantitative, longitudinal approach with census sampling, employing basic statistical tools, time series analysis, and the linear trend equation to project future scenarios for the next six academic cycles. The data obtained reveal fluctuations in enrollment over the analyzed period, an upward trend in some regional centers, and a constant decline in others, as well as the predominance of female students across all academic years and centers. Finally, three lines of action are proposed to strengthen the program’s enrollment in the coming years: expanding the period of analysis to gain a broader perspective of the phenomenon; conducting ethnographic studies involving the educational community of each regional center to better understand their specific educational context; and implementing graduate follow-up mechanisms to assess the impact of the degree on their entry into teaching or the labor market.